2021
DOI: 10.1155/2021/5566398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nesting Features and Breeding Success of Turtle Dove Streptopelia turtur between Orchards and Riparian Habitats

Abstract: The European turtle dove Streptopelia turtur breeds in both farmlands and woodlands, and it is important to explore the difference in breeding ecology of this threatened game in these two ecosystem types. This study, carried out during four years (2015–2018), compares nesting features of this species and its breeding success between apple orchards and riparian vegetation in Midelt Province, Morocco. The main result revealed that the nest placement, including nesting-tree height and nest height, is similar betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 33 publications
5
13
1
1
Order By: Relevance
“…This is of great importance since Turtle doves have lost the majority of thier breeding habitats in Europe (Moreno-Zarate et al 2020; Mansouri et al 2022b), which may help in the recovery of its population in the Southern Slope of the Mediterranean. Similarly, the recorded species demonstrated a diversified trophic diet counting granivorous, insectivorous, omnivorous, carnivorous, and mixed, and these indicate the richness of foraging resources in the zone, which is of great importance for breeders during the incubation of chicks (Sommerfeld and Hennicke 2010;Barger et al 2016), as demonstrated for Turtle dove in Midelt currently (Mansouri et al 2021b).…”
Section: Discussionmentioning
confidence: 78%
“…This is of great importance since Turtle doves have lost the majority of thier breeding habitats in Europe (Moreno-Zarate et al 2020; Mansouri et al 2022b), which may help in the recovery of its population in the Southern Slope of the Mediterranean. Similarly, the recorded species demonstrated a diversified trophic diet counting granivorous, insectivorous, omnivorous, carnivorous, and mixed, and these indicate the richness of foraging resources in the zone, which is of great importance for breeders during the incubation of chicks (Sommerfeld and Hennicke 2010;Barger et al 2016), as demonstrated for Turtle dove in Midelt currently (Mansouri et al 2021b).…”
Section: Discussionmentioning
confidence: 78%
“…Only a small clutch portion was failed due to predation (main reptiles such as Horseshoe snake Hemorrhoids Hippocrepis and Montpellier snake Malpolon monspessulanus), nest desertion (because of human disturbance via pesticide pulverization, which was done two times per month), and destruction of nests via the pression of the atomizers during pesticide application. In previous studies, factors causing loss of clutches or fail of breeding success were neglected due to the large population and distribution of the serin [26,27]. In our study, we have unveiled the most threatening factors to serin breeding performances.…”
Section: Discussionmentioning
confidence: 87%
“…We checked for normality and homogeneity of variance for all variables via Kolmogorov-Smirnov test. To assess the mortality of larvae of P. pergandii, we used the independent t-test, considering the two stages as unrelated parameters [33]. The mortality among females (three stages) was tested by one-way ANOVA.…”
Section: Statisticsmentioning
confidence: 99%